Enantioselective Radical‐Polar Crossover Reactions of Indanonecarboxamides with Alkenes. Issue 12 (30th January 2020) - Zhang, Xiying; Wu, Wangbin; Cao, Weidi; Yu, Han; Xu, Xi; Liu, Xiaohua; Feng, Xiaoming
Abstract: Highly efficient asymmetric intermolecular radical‐polar crossover reactions were realized by combining a chiral N, N ′‐dioxide/Ni II complex catalyst with Ag2 O under mild reaction conditions. Various terminal alkenes and indanonecarboxamides/esters underwent radical addition/cyclization reactions to afford spiro‐iminolactones and spirolactones with good to excellent yields (up to 99 %) and enantioselectivities (up to 97 % ee ). Furthermore, a range of different radical‐mediated oxidation/elimination or epoxide ring‐opening products were obtained under mild reaction conditions. The Lewis acid catalysts exhibited excellent performance and precluded the strong background reaction. Abstract : Crossing over : A highly efficient asymmetric radical‐polar crossover reaction of indanonecarboxamides/esters and various electron‐rich alkenes was realized by combining a chiral N, N ′‐dioxide/Ni II complex catalyst with Ag2 O. Five types of products could be obtained with good to excellent yields and ee values.